2014
DOI: 10.4315/0362-028x.jfp-14-042
|View full text |Cite
|
Sign up to set email alerts
|

Activity Retention after Nisin Entrapment in a Polyethylene Oxide Brush Layer

Abstract: The cationic, amphiphilic peptide nisin is an effective inhibitor of gram-positive bacteria whose mode of action does not encourage pathogenic resistance, and its proper incorporation into food packaging could enhance food stability, safety, and quality in a number of circumstances. Sufficiently small peptides have been shown to integrate into otherwise nonfouling polyethylene oxide (PEO) brush layers in accordance with their amphiphilicity and ordered structure, including nisin, and we have recently shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…10 Converse to antibiotics, their mode of action does not encourage pathogenic resistance, hence, suppresses the evolution of new infectious diseases. 11 In last decade, nisin has been either incorporated into various polymer matrices, for instance polyethylene brushes, 12 LDPE, 13 polypropylene, 14 soy protein, 15 or starch, 16 or in coatings over them [17][18][19] _ENREF_17. However, these direct applications have been limited in their benecial effects and exhibit a loss in long-term activity.…”
Section: Introductionmentioning
confidence: 99%
“…10 Converse to antibiotics, their mode of action does not encourage pathogenic resistance, hence, suppresses the evolution of new infectious diseases. 11 In last decade, nisin has been either incorporated into various polymer matrices, for instance polyethylene brushes, 12 LDPE, 13 polypropylene, 14 soy protein, 15 or starch, 16 or in coatings over them [17][18][19] _ENREF_17. However, these direct applications have been limited in their benecial effects and exhibit a loss in long-term activity.…”
Section: Introductionmentioning
confidence: 99%
“…Water sorption and diffusion in amphiphilic block copolymers (BCPs) are of interest for a wide range of applications 4 , including fuel cells 5 and air batteries [6][7][8][9] , CO2 separation [10][11][12][13] , water desalination 14,15 , food packaging 16,17 , drug delivery 18 , and biomedical implants 19 . Proton exchange membrane fuel cells and air batteries rely on a solid polymer electrolyte to separate the electrodes and conduct ions.…”
Section: Introductionmentioning
confidence: 99%
“…The authors demonstrated that the coating treatment did not affect the mechanical properties of poly(lactic acid); however, the gas barrier properties measured as CO2 permeation were adversely affected. In another work, the antimicrobial peptide nisin was entrapped in polyethylene oxide brushes grown on silane modified silicon wafers [61]. It was hypothesized that the polyethylene oxide brushes would protect nisin from being eluted by foreign proteins and subsequently losing its activity.…”
Section: Antimicrobialmentioning
confidence: 99%